1992
DOI: 10.1103/physrevlett.69.840
|View full text |Cite
|
Sign up to set email alerts
|

Weak ferromagnetism in κ-(ET)2Cu[N(CN)2]Cl, where (ET) is bis(ethylenedithio)tetrathiafulvalene

Abstract: Magnetization measurements at ambient pressure on /c-(ET)2Cu[N(CN)2]Cl, an organic salt that is superconducting under pressure (TV = 12.8 K at 0.3 kbar), reveal an antiferromagnetic transition near 45 K and, for the first time in this class of materials, a transition near 22 K to a state displaying weak ferromagnetic hysteresis with a saturation moment of (8x 10~4)/Wformula. This low-temperature state is characterized by a sequence of first-order magnetization jumps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(57 citation statements)
references
References 20 publications
1
56
0
Order By: Relevance
“…The electronic structure is two dimensional, layers of ET molecules are separated by polymeric anion layers (Figure 1). Judged from the electrical and magnetic properties of non-irradiated κ-ET 2 -Cl, the following temperature ranges are distinguished: (i) Below T N = 23 K: weakly ferromagnetic insulator [3]; (ii) Between 23 and about 50 K: a smooth insulator to a semiconductor transition with an anomalous magnetic field dependent magnetism; (iii) Above 50 K: semiconductor with a very small gap and a temperature-independent paramagnetic susceptibility [4]. In all three temperature ranges the coupling between layers is extremely weak: in ranges (i) and (ii) magnetic oscillations of adjacent layers are independent in general direction magnetic fields; In range (iii) electron hopping between layers is extremely rare.…”
Section: Introduction κ-(Bedt-ttf) 2 Cu[n(cn)mentioning
confidence: 99%
“…The electronic structure is two dimensional, layers of ET molecules are separated by polymeric anion layers (Figure 1). Judged from the electrical and magnetic properties of non-irradiated κ-ET 2 -Cl, the following temperature ranges are distinguished: (i) Below T N = 23 K: weakly ferromagnetic insulator [3]; (ii) Between 23 and about 50 K: a smooth insulator to a semiconductor transition with an anomalous magnetic field dependent magnetism; (iii) Above 50 K: semiconductor with a very small gap and a temperature-independent paramagnetic susceptibility [4]. In all three temperature ranges the coupling between layers is extremely weak: in ranges (i) and (ii) magnetic oscillations of adjacent layers are independent in general direction magnetic fields; In range (iii) electron hopping between layers is extremely rare.…”
Section: Introduction κ-(Bedt-ttf) 2 Cu[n(cn)mentioning
confidence: 99%
“…The κ-(BEDT-TTF) 2 X materials serve as prime examples in this regard, spanning from the Fermi-liquid metal X = Cu[N(CN) 2 ]Br, that superconducts below 12 K, to the first realization of a spin-liquid system found in X = Cu 2 (CN) 3 , with no magnetic order down to lowest temperatures despite the strong exchange interaction of J = 250 K within the triangular lattice. In the present work we take a closer look at the Mott insulator X = Cu[N(CN) 2 ]Cl, which shows canted-spin antiferromagnetic ordering, i.e., weak ferromagnetism at temperatures below 30 K [4][5][6][7] (although first experiments showed antiferromagnetism below 45 K, all subsequent measurements revealed the antiferromagnetic ordering and canting in the temperature range 20-30 K).…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic field is provided by a copper solenoid which is equipped with a movable shim coil in order to obtain a perfect balance of the SQUID detection coils. The 50 Oe maximum field of our copper solenoid is not sufficient to detect the AF (antiferromagnetic) transition which Welp et al [6] have seen at 45 K (and which, according to the resistance anomaly in Fig. lc may also occur at somewhat lower temperatures), but we can of course detect the weak ferromagnetic transition around 20 K. We observe a ferromagnetic remanence which always develops in the α-c plane, the conducting plane of the crystal.…”
Section: Resultsmentioning
confidence: 82%
“…A detailed investigation of the resistivity versus temperature at different pressures was performed by Sushko et al [4], who later also found the first indication of the reentrant behaviour in the SC state [5]. We have investigated in detail the magnetic and diamagnetic properties of the Cl-crystal, chiefly in order to study how the reported magnetic ordering phenomena (antiferromagnetism below 45 K and weak ferromagnetism below 22 K [6]) change as a function of pressure.…”
Section: Introductionmentioning
confidence: 99%